(untitled) - Reginald W Herschy (London, 1995)
The book deals with all aspects of establishing, operating and maintaining streamflow measurement stations to ensure they provide maximum information. These data are then used to plan and design efficient and cost-effective projects and developments. The book covers both traditional methods of data collection and methods involving the use of new and advanced technology. It provides hydrologists nad engineers with a complete reference from which to establish accurate and reliable flow measurement information
Keywords: hydraulic engineering